Jasmine Toguchi, mochi queen - Florence, Debbi Michiko (Florence, Debbi Michiko. Jasmine Toguchi, 2017)
Eager to do something her big sister has not done first, Jasmine Toguchi, eight, decides to pound mochi with the men and boys when her family gets together for New Year's.